STRATEGI PENGEMBANGAN PASAR TRADISIONAL DI PASAR MELATI, KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA: STRATEGY FOR DEVELOPING TRADITIONAL MARKETS IN THE JASMINE MARKET, SUNGAI RAYA SUB-DISTRICT KUBU RAYA DISTRICT - deka fardilah; Erlinda Yurisinthae; Marisi Aritonang (Agribusiness Study Program, Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Traditional markets are a favorite place for people, especially the lower and middle classes to meet their daily needs. The purpose of this study is to analyze traditional markets development strategies. In this study using descriptive qualitative research which aims to describe phenomena regarding issues of traditional market developments in the jasmine market. The analysis process begins with identifying internal and external factors using SWOT analysis. Namely strengths, weaknesses, opportunities and threats. The population of this study includes traditional market services and traders in the jasmine market because it is a wholesale market in Sungai Raya sub-district, the sample of this study involving 35 pople as a determinant of the sample. The results of the study show that the strategy for developing traditional markets in Kubu Raya district uses SWOT analysis to evaluate environmental opportunities and challenges, also analyzes the existence of two business environmental factors, where the internal environment is a strength, a condition, a situation, an event that is interconnected where has the ability to control it, and the external environment is a force, a condition, a circumstance, an event that is interconnected which has no ablitiy or little ablitiy to control or influence.